Identifikasi Program Pengentasan Kemiskinan Di Kelurahan Malabro Kecamatan Teluk Segara Kota Bengkulu Menggunakan Model Center Of Islamic Business And Ekonomic Studies (CIBEST) - Nilda Susilawati (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2019)
This study aims to identify poverty alleviation programs in the Malabro village in the Sagara Bay of Bengkulu as a sample of poverty alleviation programs in the city of Bengkulu. This research is a qualitative research combined with the analysis of the CIBEST model. The results of this study found that 95.26% of families are materially poor and spiritually rich and 4.74 families are materially rich and spiritually rich. While the poverty alleviation program is carried out with the distribution of consumptive zakat funds, distribution of productive long-term zakat funds, working capital assistance for poor households, scholarship assistance for poor children, entrepreneurship motivation training and increased business competitiveness for youth youth groups, empowering fishermen wives through training in processing fish catches, and home garden land use through hydroponic training.